KREATIVITAS GURU FIQIH DALAM MENINGKATKAN KETERAMPILAN BELAJAR SISWA - Lezi Heryanto; Ahmad Dibul Amda; Dina Hajja Ristianti (Institut PTIQ Jakarta, 2020)
This study aimed at finding out the depiction of Fiqh teacher’s creativities in improving students’ learning skills. The present study applied a qualitative approach by engaging the Fiqh teacher at Madrasah Aliyah Baitul Makmur in Curup Utara District as the key informant. The data were garnered from observations and interviews. Once the data were collected, the data were further analyzed using the theory proposed Miles et al comprising data reduction, data presentation, verification, and conclusion drawing. It seemed that the Fiqh teacher’s creativities at MA Baitul Makmur in teaching were very good. This was evident that in teaching the teacher applied various methods and used various media in order that the Fiqh-related materials could be delivered in interesting ways and could trigger comfortable learning situations alongside lowering students’ boredom in the classroom. The teacher’s evaluation in viewing students’ abilities to learn was conducted in various ways. That ranged from written and spoken assessments, portfolio, and practice-based assessments. With the Fiqh teacher’s creativities at MA Baitul Makmur, students' learning skills gain improvement.